Myocardial infarctions involving acute left circumflex occlusion: are all occlusions created equally?. (October 2010) - Stribling, Warren Kyle; Abbate, Antonio; Kontos, Michael; Vetrovec, George W; Lotun, Kapildeo
Compared with the right coronary and left anterior descending arteries, myocardial infarctions (MI) involving the left circumflex artery (LCx) have not been well described. Studies show an inconsistency in presentation of acute LCx occlusions leading to MI, which is thought to be due to electrocardiogram (ECG) insensitivity in this field. Acute occlusions of the LCx present as non-ST elevation MI (NSTEMI) as often as STEMI, but few studies have compared these presentations to determine whether ECG changes have an effect on outcomes and infarct size. While ECG insensitivity may play a role in the presentation of acute LCx occlusion, other factors such as myocardium at risk and overlapping blood supply also may be of importance.